(untitled) (The Strategic Review for Southern Africa, 2020)
With issue No 1/2013, this journal changed in several respects. Under a new editor-in-chief, the Strategic Review for Southern Africa, then published for 35 years, turned into an open access journal with a redesigned look. But the makeover aimed at more than merely cosmetic changes. As outlined in the introduction of that issue, the changing context both in South Africa as well as globally, motivated a conceptual re-positioning, that also modified the subject-related thematic framework1). Since then, thanks to many contributors offering a wide range of topical analyses, we hopefully managed to live up to at least some of the expectations created. After five years, it is now time to hand editorial responsibility to a new generation of scholars groomed in the spirit of democratic South Africa. This, therefore, is the last issue for me as the editor-in-chief. While I welcomed the privilege to lead the journal towards implementing a modified agenda, I now welcome the opportunity to move out of the way and pursue other tasks. I thank all those in the editorial group and the advisory board who accompanied and supported me during the last years. I am especially grateful to Maxi Schoeman, who felt I would be the right choice for this task. Special thanks go also to Wilma Martin, without her assistance none of the last eleven issues would have become a reality.